2019
DOI: 10.1111/ijcp.13408
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nocturia on patients' health‐related quality of life and healthcare resource utilisation compared with OAB and BPH: Results from an observational survey in European and American patients

Abstract: Objective To evaluate the impact of nocturia on patients' quality of life and healthcare resource utilisation (HRU) compared with overactive bladder (OAB) and benign prostatic hyperplasia (BPH). Methods Data were drawn from a multinational (France, Germany, Spain, UK and US) survey of physician and patient‐reported outcomes. The patient groups of interests were those diagnosed with only nocturia, with only OAB, and with only BPH. Health‐related quality of life (HRQoL) and productivity measures were derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…19 Zeng et al reported that nocturia patients presented as having a significantly reduced quality of life, reduced work productivity and increased utilization of healthcare resources when compared with OAB and/or BPH. 20 Theerawirojana et al reported a correlation between bladder capacity and lower urinary tract symptoms after renal transplantation and concluded that nocturia and nocturnal polyuria are characteristics of lower urinary tract function after renal transplantation, and are probably associated with long term anuria during hemodialysis and small bladder capacity. Quality of life was not impacted by lower urinary tract symptoms evidenced by a low symptom score for most patients.…”
Section: Discussionmentioning
confidence: 99%
“…19 Zeng et al reported that nocturia patients presented as having a significantly reduced quality of life, reduced work productivity and increased utilization of healthcare resources when compared with OAB and/or BPH. 20 Theerawirojana et al reported a correlation between bladder capacity and lower urinary tract symptoms after renal transplantation and concluded that nocturia and nocturnal polyuria are characteristics of lower urinary tract function after renal transplantation, and are probably associated with long term anuria during hemodialysis and small bladder capacity. Quality of life was not impacted by lower urinary tract symptoms evidenced by a low symptom score for most patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although nocturia can have multiple causes, the most common is nocturnal polyuria-overproduction of urine at night [4]. Lifestyle modifications are the first intervention for the management of nocturia but as symptoms progress, such measures may be inadequate, and pharmacotherapy warranted [3,[5][6][7][8][9][10]. Nocturia has a pronounced negative impact on patient QoL [8,[11][12][13] and is associated with reduced work productivity, more frequent physician visits, socioeconomic burden [5,6,10,12,14], sleep impairment [15,16], higher risk of falls and fractures, depression, and increased mortality [3,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle modifications are the first intervention for the management of nocturia but as symptoms progress, such measures may be inadequate, and pharmacotherapy warranted [3,[5][6][7][8][9][10]. Nocturia has a pronounced negative impact on patient QoL [8,[11][12][13] and is associated with reduced work productivity, more frequent physician visits, socioeconomic burden [5,6,10,12,14], sleep impairment [15,16], higher risk of falls and fractures, depression, and increased mortality [3,17,18]. There has, however, been an unmet need for a validated, reliable, and specific patient-reported instrument to assess the impact of nocturia on patient QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Nocturnal polyuria, recently defined as excessive production of urine during an individual's main sleep period and previously defined as overproduction of urine at night (>20%‐33% of total 24‐hour urine volume, depending on age), 1 is a frequent contributor to and is present in most patients with nocturia 3 . Nocturia negatively affects quality of life (QoL), 5‐7 with greater QoL effects seen with increasing frequency of nocturnal voids 6,8,9 . The impact on QoL is often due to sleep disruption caused by frequently waking at night to void, with associations seen between nocturia and subjective and objective sleep quality 3,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…most patients with nocturia. 3 Nocturia negatively affects quality of life (QoL), [5][6][7] with greater QoL effects seen with increasing frequency of nocturnal voids. 6,8,9 The impact on QoL is often due to sleep disruption caused by frequently waking at night to void, with associations seen between nocturia and subjective and objective sleep quality.…”
mentioning
confidence: 99%